Financial Analytic Model as a Management Innovation for Nonpublic Russian Companies - Ирина Николаевна Долматова (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
In the conditions of increasing competition and globalization on the Russian markets the new demands and performance results criteria are applied to the companies irrespective their business structure and entity. In case your company is in the phase of growth and active investments, there is a necessity for alternative (in comparison to conventional) accounting tools to evaluate performance results as well as to administrate everyday activities. Using of Financial analytic model for private business in Russia in most cases is an essential novelty, unconventional approach or management innovation. The question of applicability and relevance of common finance analytics methods to a Russian nonpublic private company, their adaptability to actual business practice remains still open-ended and forms the main theme of the present article. Association Versivo, Samara Board of Directors, Personnel and incentive payments committee, Chairman E-mail: dolmatova@versivo.ru